2022
DOI: 10.3390/plants11192544
|View full text |Cite
|
Sign up to set email alerts
|

The Alleviation of Metal Stress Nuisance for Plants—A Review of Promising Solutions in the Face of Environmental Challenges

Abstract: Environmental changes are inevitable with time, but their intensification and diversification, occurring in the last several decades due to the combination of both natural and human-made causes, are really a matter of great apprehension. As a consequence, plants are exposed to a variety of abiotic stressors that contribute to their morpho-physiological, biochemical, and molecular alterations, which affects plant growth and development as well as the quality and productivity of crops. Thus, novel strategies are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 154 publications
0
4
0
1
Order By: Relevance
“…There are cellular characteristics that facilitate the life of metallophytes, associated with the efficiency of the antioxidant defence system that faces oxidative stress, maintaining cellular redox homeostasis through the synchronous action of several enzymes (SOD, CAT, POD, APX, and GR) and non-enzymatic antioxidants (AsA and GSH), as well as ROS transformation pathways. These mechanisms form the basis for adaptation to excessive amounts of heavy metals [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are cellular characteristics that facilitate the life of metallophytes, associated with the efficiency of the antioxidant defence system that faces oxidative stress, maintaining cellular redox homeostasis through the synchronous action of several enzymes (SOD, CAT, POD, APX, and GR) and non-enzymatic antioxidants (AsA and GSH), as well as ROS transformation pathways. These mechanisms form the basis for adaptation to excessive amounts of heavy metals [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results showed that the leaves of P. graveolens can be safely exploited as an herbal raw material which can be used for the extraction of bioactive compounds, the biosynthesis of which might be stimulated by plant exposure to Cu. On the other hand, the review paper of Labudda et al [7] showed the significance of basic sciences in the development of applied sciences. According to the authors, the understanding of plant adaptation and acclimation mechanisms in response to harsh conditions is necessary to relieve the pressure of environmental changes and ensure global food security for an increasing population, as well as to restore areas degraded by human activity.…”
Section: Chemical Elements' Stressmentioning
confidence: 99%
“…org/10.33448/rsd-v11i14.36285 3 necrose e morte da planta (Zhang e Li, 2019). Observou-se que as interconversões entre Cu ++ e Cu + podem gerar espécies reativas ao oxigênio (ROS), moléculas que danificam as membranas e várias estruturas biológicas, como DNA, lipídios e proteínas (Labudda et al, 2022).…”
Section: Absorção De Cobreunclassified